Dampak Rating dan Ulasan terhadap Perkembangan Kedai Tempo Doloe Kota Bengkulu - Kurniawan, Andri; Nengsi, Elta Putri Setia; Wulandari, Ardeya; Lorensya, Cintia Novita; Wicaksono, Rama Iqbal; Fitriah; Alam, RG Guntur (Pakis Journal Institute, 2025)
The development of the culinary business in the digital era demands business actors to optimize online platforms in building brand image and increasing competitiveness. One of the important elements in this digital ecosystem is customer ratings and reviews, which can influence prospective consumers’ perceptions and business sustainability. This study aims to analyze the impact of customer ratings and reviews on the development of Kedai Tempoe Doloe in Bengkulu City. This research employed a descriptive qualitative approach, with data collected through questionnaires distributed to 40 customers and semi-structured interviews with the shop manager. The data obtained were analyzed using thematic analysis and frequency distribution percentage calculations. The results showed that the majority of customers gave positive ratings in aspects of service (55% very satisfied), food taste (62.5% very satisfied), shop atmosphere (45% very satisfied), cleanliness (50% very satisfied), and facilities (42.5% very satisfied), with an overall satisfaction rate (Very Satisfied + Satisfied) of 84%. Customers’ favorite menus were Cuanki Doeloe (37.5%), Bakmi Ayam (25%), Ubi Brullee (17.5%), Teh Solo (12.5%), and Cireng (7.5%). These findings were supported by interview results indicating the need for improvements in complementary facilities and seating comfort during peak hours. In conclusion, customer ratings and reviews play a strategic role in the evaluation process, decision-making, and service development of culinary businesses at Kedai Tempoe Doloe.